2009
DOI: 10.1002/ddrr.65
|View full text |Cite
|
Sign up to set email alerts
|

“Family matters:” Fetal alcohol spectrum disorders and the family

Abstract: Information about ''family matters'' is vital to developing targeted interventions, reducing placement disruption, and enhancing outcome in fetal alcohol spectrum disorders (FASD). The quality of the caregiving environment and family function are associated with long-term outcome in natural history study of individuals with FASD. This article integrates multiple information sources to better understand the role of family factors in the outcome of individuals with FASD, and how the family is affected by raising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
122
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 55 publications
7
122
1
Order By: Relevance
“…2;2014 themselves as significantly worse than the norm on School Problems and Inattention/Hyperactivity on the BASC-2. These results are consistent with other research, which has shown that academic difficulties as well as ADHD (Olson et al, 2009) are a significant area of concerns among adolescents with PAE, and may again reflect greater awareness of behavior that is external, concrete, and often the subject of external feedback (e.g. consequences).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…2;2014 themselves as significantly worse than the norm on School Problems and Inattention/Hyperactivity on the BASC-2. These results are consistent with other research, which has shown that academic difficulties as well as ADHD (Olson et al, 2009) are a significant area of concerns among adolescents with PAE, and may again reflect greater awareness of behavior that is external, concrete, and often the subject of external feedback (e.g. consequences).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the high rates of co-morbid psychiatric diagnoses among individuals with PAE (Pei et al, 2011), although surprising to see the low rate of reported anxiety concerns given the high rate of anxiety disorders reported for this population (Olson et al 2009). It is also noteworthy that it was the externalizing concerns, such as antisocial behavior and aggression that were described as the greatest concerns, as opposed to internalizing disorders.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These effects are collectively known as Fetal Alcohol Spectrum Disorders (FASD). These disorders are estimated to affect approximately 2-5% of live-births in the United States and some Western European countries (May et al, 2009), and the effects have lifelong implications for the affected individuals, their families, and their communities (Lupton, Burd, & Harwood, 2004;Olson, Oti, Gelo, & Beck, 2009;Streissguth, Barr, Kogan, & Bookstein, 1997). Strategies to prevent prenatal alcohol exposure include broad awareness-raising initiatives that target individuals' knowledge, beliefs, and attitudes, and seek to create and reinforce a social context conducive to alcohol abstinence (Deshpande et al, 2005).…”
Section: Introductionmentioning
confidence: 99%